Next-generation Probiotics for Human Health: A Critical Narrative Review of Mechanisms, Clinical Translation, Safety and Precision Microbiome Therapeutics - Sandhya Dhyani; Himani Belwal; Neetu Dobhal (European Journal of Nutrition & Food Safety, 2026)
The term next-generation probiotic (NGP) is increasingly used for health-associated gut commensals and rationally engineered microorganisms developed from microbiome science rather than from the historical food-fermentation route that produced most conventional probiotics. This expansion has created a translational opportunity, but also a recurrent evidential problem: taxonomic association, mechanistic plausibility, preclinical efficacy, human safety and clinical benefit are often treated as if they formed a single continuum of proof. This critical narrative review evaluates the evidence for NGPs as human-health interventions, with emphasis on natural candidates including Akkermansia muciniphila, Anaerobutyricum soehngenii, Faecalibacterium prausnitzii, Butyricicoccus pullicaecorum, Christensenella minuta, selected Bacteroides and Parabacteroides strains, and on engineered live biotherapeutic products. Literature published from 1 January 2004 to 19 June 2026 was considered, with foundational and methodological sources included where necessary. The most persuasive direct human evidence currently concerns cardiometabolic endpoints for A. muciniphila and A. soehngenii, yet effect sizes are generally modest, trials remain relatively small, and recent findings indicate that baseline microbiome composition can determine colonisation and response. For F. prausnitzii, B. pullicaecorum, C. minuta and several Bacteroidota candidates, mechanistic or safety evidence is stronger than evidence of clinical efficacy. Engineered strains provide a different translational model: they can deliver defined metabolic functions in vivo, but early human studies have primarily established safety and pharmacodynamic activity rather than durable clinical benefit. Across the field, oxygen sensitivity, manufacturing reproducibility, strain-level safety, antimicrobial-resistance surveillance, dose and formulation, ecological persistence, endpoint selection and regulatory classification remain decisive constraints. The available evidence therefore supports NGPs as a credible precision-therapeutic platform rather than as a broadly validated class of health-promoting products. Progress will depend on confirmatory multicentre trials, prospective responder stratification, standardised potency measures and long-term ecological safety assessment.